AplikasiDecanter solid dengan Pupuk NPK Tablet Terhadap Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) di TBM-IIasal Kecambah Kembar - Simbolon, Fresby Junianto; Zuhry, Elza; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to determine the influence of application of solid decanter and tabletNPK and get a combination is best for plant growth palm oil that comes from twin sprouts in Two-year-old Immature Oil Palm. Research has been carried out at the Experimental Farm Faculty of Agrotechnology, University of Riau, Rimbo, Kampar Regency, Riau Province. Research was conducted from December 2017 until March 2018.The research was carried out experimentally using Compeletely Randomize Block Design (RAK) consisting of 5 treatments: P0 (without fertilizers), P1 (Solid decanter 1.430 t. ha-¹ + NPK 8 tablets per plant), P2 (Solid decanter 1.430 t. ha-¹ + NPK 10 tablets per plant), P3 (Solid decanter 2.145 t. ha-¹ + NPK 8 tablets per plant), P4 (Solid decanter 2.145 t. ha-¹ + NPK 10 tablets per plant). The observed parameters were a plant height, number of leaves, petiolelength and stems circumference. The data obtained were analyzed statistically using the analysis of variance and Duncan at the 5 % level.The results showed that the application of various dosages of NPK fertilizer with solid decanter tablet gives added influence on plant height, stem length, number of leaves, petiolelength and the circumference of the stem of the plant oil palm seedling origin in twins TBM II. Application of 2.145 t. ha-1 solid decanter with 10 tablets ofNPK gave the best combination of all of the parameters.Keywords: Palm Oil, Twin sprouts, Solid decanter, Tablets NPK.